ENHANCING FACILITATION COMPETENCIES OF FUTURE EDUCATION TEACHERS THROUGH THE CREDIT MODULE SYSTEM - Khamidova Sabrina Abduvahobovna (American Journals, 2024)
This article delves into the necessity and strategies for enhancing the facilitation competencies of future education teachers through the utilization of the credit module system. The modern educational landscape demands pedagogical approaches that equip teachers with the necessary skills to facilitate effective learning experiences. By integrating the credit module system into teacher education programs, educators can develop a versatile skill set crucial for engaging diverse learners in various educational settings. This article discusses the significance of facilitation competencies, explores the benefits of the credit module system, and proposes effective strategies to optimize the development of future education teachers.
Keywords: Facilitation competencies, future education teachers, credit module system, teacher education, pedagogy